Attention Deficit Hyperactivity Disorder (ADHD) among Children Aged 6 to 17 Years Old Living in Girja District, Rural Ethiopia - Hirbaye Mokona Lola; Habte Belete; Abebaw Gebeyehu; Aemro Zerihun; Solomon Yimer; Kassech Leta (Behavioural Neurology)
Objective. Attention deficit hyperactivity disorder (ADHD) is one of the most common behavioral disorders in childhood with long-term outcomes. Although ADHD is the most studied behavioral disorders of childhood in developed countries, few studies have been conducted in Ethiopia. The aim of this study was to determine the prevalence of ADHD in rural parts of Ethiopia. Method. A cross-sectional study was conducted from May to June 2015 among children aged 6 to 17 years living in rural areas. A multistage cluster sampling technique was used to select 1302 participants. The Disruptive Behavior Disorder Rating Scale was used to collect the data. Logistic regression analysis was used to see statistically significant variables. Result. The prevalence rate of attention deficit hyperactivity disorder (ADHD) among children was 7.3%. Being male (Adjusted Odds Ratio (AOR) = 1.81, 95% CI: (1.13, 2.91)); living with a single parent (AOR = 5.0, 95% CI: (2.35, 10.65)); child birth order/rank (AOR = 2.35, 95% CI: (1.30, 4.25)); and low family socioeconomic status (AOR = 2.43, 95% CI: (1.29, 4.59)) were significantly associated with ADHD. Conclusion. The ADHD prevalence rate was found to be similar with global reports. Prevention and early management of maternal complications is important to reduce the prevalence of ADHD among children.